2021
DOI: 10.2495/tdi-v5-n1-41-56
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Longitudinal Train Dyna Mics Code for Time Domain Simulations and Modal Analyses

Abstract: Large speeds and axle-loads are required for modern freight trains, which can cause a big rise in in-train forces on wagon coupling elements for both tensile and compressive states, thus possibly leading to breaking of the coupling systems and to train derailments, respectively. Therefore, longitudinal train dynamics (LTD) simulations are a key tool for the prediction of the in-train forces and for the design of coupling and braking systems as well as for the optimization of the train composition. LTD simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In trains the longitudinal forces sometimes reach a value exceeding the strength of the frame of some wagon designs. Studies have shown that the large values of impact and tractive forces are due mainly to the sudden starting of the train; the in draught of a partially compressed train, especially with a fully uncompressed tail end having wagons with brakes not released; and braking by a stop-crane in the train tail end at a low speed and a compressed train at the beginning of braking [15][16][17][18].…”
Section: Strength Of Rolling Stock Elementsmentioning
confidence: 99%
“…In trains the longitudinal forces sometimes reach a value exceeding the strength of the frame of some wagon designs. Studies have shown that the large values of impact and tractive forces are due mainly to the sudden starting of the train; the in draught of a partially compressed train, especially with a fully uncompressed tail end having wagons with brakes not released; and braking by a stop-crane in the train tail end at a low speed and a compressed train at the beginning of braking [15][16][17][18].…”
Section: Strength Of Rolling Stock Elementsmentioning
confidence: 99%
“…The authors' research group developed in past activities the in-house MATLAB LTDPoliTo code [6][7][8], which was validated on the simulation scenarios proposed in the context of the international benchmark of LTD simulators [9,10] (''the benchmark'' in the rest of the paper). However, the LTDPoliTo code in its original form does not consider the braking forces due to the air brake system, as the air brake forces were outside the scope of the benchmark and only dynamic braking forces provided by the locomotives were considered.…”
Section: Introductionmentioning
confidence: 99%
“…The tool can investigate stop and drag braking operations, 1Bg and 2Bg block configurations as well as different brake shoe materials, however the preliminary results presented in the next section only refer to drag braking operations and traditional P10 cast iron brake shoes. The Matlab routine solves both the longitudinal train dynamics (LTD) equation and the rotational equilibrium equation for the braked wheel, based on an existing LTD code [18][19][20][21] and an existing heuristic wheel-rail adhesion model [22][23][24][25] developed in past activities. Starting from the results computed by the Matlab routine, which for drag braking operations correspond to wheel-shoe pressing force and friction coefficient, the FE contact module calculates the distribution of the normal and tangential pressure at the wheel-shoe interface, thanks to the application of ANSYS 2D surface-to-surface contact elements CONTA172 and TARGE169, solving the problem with the augmented Lagrangian method [26].…”
Section: Methodsmentioning
confidence: 99%